(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The aim of the study was to evaluate the Alllium cepa for its pharmacognostical properties and for its hair growth promoting activity. Macroscopical study of Allium cepa showed that Allium cepa having white brown colour, pungent odour, acrid in taste and bulb and roots are angular in shape. The microscopical evaluations of fresh bulb showed that it contains characteristic features of stomata, presence of upper and lower epidermis, vascular tissues such as xylem and phloem, palisade tissue, cork cell, starch grain and calcium co-oxalate crystals. Total Ash value taken to be 8.5 %, acid soluble ash was found to be 2.5 %, water soluble ash taken to be 0.75%. Animal study showed that Allium cepa initiates the hair growth on day 6 and showed complete hair growth on day 20, which was compared with the standard drug Monoxidil. The pure juice of Allium cepa is found effective as that of standard drug Minoxidil for the hair growth in albino rats.